1997
DOI: 10.1164/ajrccm.155.4.9105069
|View full text |Cite
|
Sign up to set email alerts
|

The relations between expiratory chest CT using helical CT and pulmonary function tests in emphysema.

Abstract: Chest computed tomography (CT) and pulmonary function tests are usually used for the evaluation of emphysema. We performed the present study to evaluate more accurately the relationship between the degree of morphological change and the functional abnormality in emphysema. We used a helical CT apparatus to obtain the CT images both at full inspiration and full expiration. We classed the degree of emphysema into 5 grades (0-4) by visual observation on CT image obtained at the two levels, upper and lower fields,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 30 publications
5
57
0
1
Order By: Relevance
“…It was concluded that expiratory CT reflects expiratory airflow limitation and the subsequent air trapping more than reduction of the alveolar wall surface. These findings were confirmed by EDA et al [59] and by LAMERS et al [60] who also found higher correlations between PFTs reflecting the airflow obstruction and CT data obtained in expiration than in inspiration, whereas the correlations between diffusing capacity and CT data were similar.…”
Section: Factors Influencing Computed Tomography Densitometrysupporting
confidence: 69%
See 1 more Smart Citation
“…It was concluded that expiratory CT reflects expiratory airflow limitation and the subsequent air trapping more than reduction of the alveolar wall surface. These findings were confirmed by EDA et al [59] and by LAMERS et al [60] who also found higher correlations between PFTs reflecting the airflow obstruction and CT data obtained in expiration than in inspiration, whereas the correlations between diffusing capacity and CT data were similar.…”
Section: Factors Influencing Computed Tomography Densitometrysupporting
confidence: 69%
“…In summary, expiratory CT is thus not as adequate as inspiratory CT for measuring the extent of pulmonary emphysema. This conclusion suggests that possible errors, secondary to variations of lung volume at which the CT scans are obtained, could be avoided by using spirometric triggering [53][54][55]59]. …”
Section: Factors Influencing Computed Tomography Densitometrymentioning
confidence: 99%
“…They speculated that abnormalities in the expiratory CT are more reflective of air trapping than of a genuine reduction in terminal airspace volume. EDA et al [33] found that the helical CT images acquired at full expiration reflect air trapping and that CT visual scores at full inspiration showed significant correlation with emphysema. The cut-off point between areas of normal lung density and LAAs used was -950 HU.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cross sectional studies [14,31,32,51] have shown moderate, statistically significant, inverse correlations between CT measures of severity of emphysema and both FEV1 and carbon monoxide diffusing capacity. For FEV1, the coefficient of correlation (r) ranged -0.41--0.57; for diffusing capacity, r was higher, ranging -0.54--0.65.…”
Section: Clinical Significance Of Computed Tomography Indices Of Emphmentioning
confidence: 99%